Centrosome Positioning in Dictyostelium: Moving beyond Microtubule Tip Dynamics - Michael P. Koonce; Irina Tikhonenko (Cells, 2018)
The variability in centrosome size, shape, and activity among different organisms provides an opportunity to understand both conserved and specialized actions of this intriguing organelle. Centrosomes in the model organism Dictyostelium sp. share some features with fungal systems and some with vertebrate cell lines and thus provide a particularly useful context to study their dynamics. We discuss two aspects, centrosome positioning in cells and their interactions with nuclei during division as a means to highlight evolutionary modifications to machinery that provide the most basic of cellular services.